The Female Half Of The Imperial Palace at Persepolis: Architecture and Functional Lay-Out: _________________________________ - Sil’nov, Aleksandr V. (Acta Archaeologica Lodziensia, 2019)
This article is devoted to architectural features of the well-known palace complex of the Achaemenid dynasty at Persepolis. On the basis of the relevant archaeological material, the author presents various possible reconstructions incorporating architectural fragments from the so-called harem of Xerxes, including ones of its exterior and interior forms. Additionally, an analysis of the functional lay-out of this part of the palace is given. For the reconstruction modern three-dimensional computer visualizations are used.